Activation of Toll-like receptor 5 in microglia modulates their function and triggers neuronal injury - Ifuku, Masataka (Acta Neuropathol Commun, 2020)
Microglia are the primary immune-competent cells of the central nervous system (CNS) and sense both pathogen- and host-derived factors through several receptor systems including the Toll-like receptor (TLR) family. Although TLR5 has previously been implicated in different CNS disorders including neurodegenerative diseases, its mode of action in the brain remained largely unexplored. We sought to determine the expression and functional consequences of TLR5 activation in the CNS. Quantitative real-time PCR and immunocytochemical analysis revealed that microglia is the major CNS cell type that constitutively expresses TLR5. Using Tlr5(−/−) mice and inhibitory TLR5 antibody we found that activation of TLR5 in microglial cells by its agonist flagellin, a principal protein component of bacterial flagella, triggers their release of distinct inflammatory molecules, regulates chemotaxis, and increases their phagocytic activity. Furthermore, while TLR5 activation does not affect tumor growth in an ex vivo GL261 glioma mouse model, it triggers microglial accumulation and neuronal apoptosis in the cerebral cortex in vivo. TLR5-mediated microglial function involves the PI3K/Akt/mammalian target of rapamycin complex 1 (mTORC1) pathway, as specific inhibitors of this signaling pathway abolish microglial activation. Taken together, our findings establish TLR5 as a modulator of microglial function and indicate its contribution to inflammatory and injurious processes in the CNS.